أثر استخدام تكنولوجيا المعلومات على الأداء الوظيفي وأداء المنظمة: دراسة تطبيقية في الشركة العامة للكهرباء بليبيا - أحمد صالح عبد اللطيف صالح
This research aimed at identifying the effect of using Information Technology on the official performance and the performance of the organization in the General Electricity of Libya. It also examined the level of the official performance of the individual workers in the General Electricity of Libya, in order to improve and develop the performance of the organization, possibility of getting significant differences (if found), according to the demographical factors. The specimen under study is made up of the individual workers in the General Electricity of Libya, while its target is to assess their administrative managements. Thus, the descriptive analytical method was adopted in carrying out the study. In order to achieve the objectives behind the study, a questionnaire was prepared with 52 items under each of three pivots (Information Technology, level of official performance and performance of the organization). A total of 330 copies of questionnaire were distributed among the individual workers in the specimen under study, while 284 retrieved and considered to have fulfilled the required condition. The percentage of the response from the society under study was 86%. Then the analysis of the items, as shown in the frequency tables, percentage, arithmetic median and standard deviation, was made; variance analysis under the Statistical Package for Social Sciences (SPSS) and path analysis (AMOS) were used, in order to know the effects of study's variables. With this, the researcher was able to come out with some results and the most important of them are that: there is an indirect effect of Information Technology on the performance of the organization through the influence of the official performance in the General Electricity of Libya; there is an effect of the elements of Information Technology on the official performance- whenever the need for keeping pace with the technological advancements arises, the competence of the individual workers (their official performance) in the company becomes high. Also, the study has come out with some recommendations which include: working on the development and modernization of Information Technology periodically, with the objective of enhancing the competence and effectiveness of the electronic services within the company; so that the size of the work in the company would be reduced- being the only company responsible for the supply of electric current in Libya, while the company should consider the opinions of the workers by holding meetings with them and involve them in the activity of taking decisions for the progress of the organization.